2008
DOI: 10.1002/nau.20644
|View full text |Cite
|
Sign up to set email alerts
|

Simulated childbirth injuries in an inbred rat strain

Abstract: Vaginal distension (VD) in outbred rats has been shown to decrease urethral resistance, as well as increase the expression of the stem cell-homing chemokine, monocyte chemotactic factor 3 (MCP-3), but not stromal derived factor 1 (SDF-1). The aim of this study was to determine if similar responses are induced by VD in an inbred rat strain. Forty female Lewis rats underwent VD or sham VD followed by leak point pressure (LPP) testing 4 or 10 days later. Ten additional rats served as controls. The urethra and vag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 33 publications
7
24
2
Order By: Relevance
“…These results are similar to two previous studies by Woo et al, 22,23 who demonstrated a noticeable up-regulation of MCP-3 in the rat urethra and vagina immediately after VD. However, in contrast to our findings, Woo et al did not observe up-regulation of MCP-3 in the bladder specimens.…”
Section: Commentsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are similar to two previous studies by Woo et al, 22,23 who demonstrated a noticeable up-regulation of MCP-3 in the rat urethra and vagina immediately after VD. However, in contrast to our findings, Woo et al did not observe up-regulation of MCP-3 in the bladder specimens.…”
Section: Commentsupporting
confidence: 93%
“…The lack of differences in rectal MCP-3 expression after VD injury in our study is consistent with the findings of Woo et al, 22,23 but is in contrast to the findings of Wood et al 13 who observed a 21-fold increase in relative MCP-3 expression in the rectum immediately after VD injury. It should be noted, however, that in the Wood study this difference was only seen after 4 hours of sustained VD injury, as there was no relative difference in MCP-3 expression after 1 hour of VD as compared to controls.…”
Section: Commentsupporting
confidence: 91%
See 1 more Smart Citation
“…A differential response of urethra CCL7 expression after VD and PNT is not surprising given the lack of continence recovery observed with PNT compared with VD. 14,15 Furthermore, these data suggest that a shear event (as occurs in the VD group), and not nerve injury only (as in the PNT model), may contribute to the observed changes in urethra CCL7 after VD. The theory of shear effect is supported by the lack of changes in SDF-1, a known marker of ischemia, and hypoxia inducible factor-1 alpha previously reported in other rodent VD models.…”
Section: Discussionmentioning
confidence: 69%
“…10-13 We have shown a substantial decrease in leak point pressure 4 days after VD with near complete recovery to baseline within 14 days has been shown in rats. 14 PNT has been shown to produce long lasting reductions in leak point pressure, up to 5 weeks after nerve transection in rats. 15 Furthermore, VD has been shown to alter urethral tissue as early as 1 hour after injury and external urethral sphincter within 4 hours.…”
Section: Introductionmentioning
confidence: 98%